A case of valence competition in elections: Parties' emphasis on corruption in electoral manifestos. (September 2015) - Curini, Luigi; Martelli, Paolo
Despite a growing interest in investigating the causes of political corruption, far less attention has been devoted to analysing the conditions under which political actors have an incentive to highlight corruption in electoral competition. Do parties talk about corruption just as a reaction to exogenous factors (i.e. scandals reported in the press)? Or are there systematic patterns in the way parties emphasize this issue during campaigns? Assuming that corruption is a valence issue (i.e. an issue universally supported/disclaimed by electors), we put our investigation in the framework of a one-dimensional model and hypothesize that spatial considerations can affect parties' incentives to emphasize corruption issues. Empirical analysis based on CMP data shows that such an incentive exists for both cabinet and non-cabinet parties, and increases with proximity on the ideological scale.